Spinal Neurofibromatosis with Central Nervous System Involvement in a Set of Twin Girls and a Boy: Further Expansion of the Phenotype - Ruggieri, Martino; Polizzi, Agata; Salpietro, Vincenzo; Incorpora, Gemma; Nicita, Francesco; Pavone, Piero; Falsaperla, Raffaele; Nucifora, Caterina; Granata, Francesca; Distefano, Angela; Padua, Luca; Caltabiano, Rosario; Lanzafame, Salvatore; Gabriele, Anna Lia; Ortensi, Andrea; D'Orazi, Valerio; Panunzi, Andrea; Milone, Pietro; Mankad, Kshitij; Platania, Nunzio; Albanese, Vincenzo; Pavone, Vito (Neuropediatrics, 2013)
Background Familial spinal neurofibromatosis is a form of neurofibromatosis 1 (NF1), consisting of extensive, symmetrical, histologically proven, multiple neurofibromas of the spinal roots at every level and of all major peripheral nerves sometimes associated with typical NF1 stigmata; most cases underlie NF1 gene mutations.Objectives The objectives of this study are (1) to report the findings in a set of 16-year-old monozygotic twin girls and a 14-year-old boy and (2) to review the existing literature.Methods and Results In this article, we report the cases of three children who (1) had manifested mildly different symptomatic neuropathy (twins, aged 4 years; and a boy, aged 9 years) associated with massive, symmetrical neurofibromas; (2) had few café-au-lait spots with irregular margins and pale brown pigmentation; (3) were presented with, at brain magnetic resonance imaging (MRI), bilateral, NF1–like high-signal abnormalities in the basal ganglia; (4) yielded missense NF1 gene mutations in exon 39; and (5) had unaffected parents with negative NF1 genetic testing as well as discuss 12 families and 20 sporadic and 5 additional cases that presented spinal neurofibromatosis within classical NF1 families (53 cases) that were reported in the literature.Conclusions This article presents the first report on (1) spinal neurofibromatosis in a set of affected monozygotic twins; (2) the earliest onset of the disease; and (3) the occurrence of high signal lesions in the brain at MRI.
Keywords: familial spinal neurofibromatosis; twins; brain abnormalities; literature review